Mechanical Recanalization following i.v. Thrombolysis: A Retrospective Analysis regarding Secondary Hemorrhagic Infarctions and Parenchymal Hematomas - J. Höltje; F. Bonk; A. Anstadt; C. Terborg; C. Pohlmann; P. P. Urban; R. Brüning (Radiology Research and Practice)
Introduction. In acute stroke by occlusion of the proximal medial cerebral artery (MCA) or the distal internal carotid artery, intravenous thrombolysis is an established treatment. Another option is mechanical recanalization. It remains unclear if the combination of both methods poses an additional bleeding risk. The aim of this retrospective analysis is to determine the proportion of hemorrhagic infarctions and parenchymal hematomas. Methods. Inclusion criteria were an occlusion of the carotid T or proximal MCA treated with full dose thrombolysis and mechanical recanalization. 31 patients were selected. Devices used were Trevo, Penumbra Aspiration system, Penumbra 3D Retriever, and Revive. The initial control by computed tomography was carried out with a mean delay to intervention of 10.9 hours (SD: 8.5 hours). Results. A slight hemorrhagic infarction (HI1) was observed in 2/31 patients, and a more severe HI2 occurred in two cases. A smaller parenchymal hematoma (PH1) was not seen and a space-occupying PH2 was seen in 2/31 cases. There was no significant difference in the probability of intracranial bleeding after successful (thrombolysis in cerebral infarctions 2b and 3) or unsuccessful recanalization. Conclusion. The proportion of intracranial bleeding using mechanical recanalization following intravenous thrombolysis appears comparable with reports using thrombolysis alone.